Vocigrafias - Nascimento, Roberta Marques do (2020)
This paper aims to study the voice as materiality and discourse in its interactions with memory based on the unexplored and untried concept of voicegraphy, initially formulated by professor Jerusa Pires Ferreira in her article “The Vigil of Oralities”. This proposition is rife with latent potential that is evoked by autobiographical memories and experiences in the family, artistic, political and academic realms. A poliphonic fabric is woven with theory, the accounts of experiences, interviews, audio and visual recordings. The articulation between these elements leads to the concrete possibility of defining voicegraphy, through its materialization, centered on the voice and its ramifications. Therefore, four axis were established. They analyze respectively: how voice relates to borderline processes, such as birth and death, addressing physiological, political and poetic aspects; the possible theoretical-affective crossings centered on the voice theme and its relations with culture, performance and memory; the creative and discursive procedures of the voices present in the documentary SLAM: Sworded words (2017); aspects of racial debate based on prominent voices at the JWTC Joannesburg Workshop of Theory and Criticism, held in South Africa in 2014. Based on theoretical framework offered by the interactions and convergences of authors Jerusa Pires Ferreira and Paul Zumthor, this paper aims to create a body of knowledge in which the diversity of views and its applications is articulated. This consistent material leads to the study of the voice in this innovative and provocative way